(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Non Alcoholic Fatty Liver Disease (NAFLD) is a reversible condition of the liver, wherein large vacuoles of triglyceride fat accumulates in liver cells via the process of steatosis, despite any evidence of excessive alcohol consumption. In view of present scenario of high prevalence and limited treatment options, this study was conducted to assess the effect of Murabba-i- Zanjabīl in NAFLD. Present study was designed as a randomized placebo controlled trial with 30 patients in test group and 10 patients in control group. Participants in test group were administered with Murabba-i- Zanjabīl, 5 gm twice daily, 30 minutes before food for 45 days and those in control group were given 1 capsule of 500 mg each containing wheat flour twice daily, 30 minutes before food for 45 days. All the participants were asked to follow up at every 15 days for assessment of subjective parameters. Objective parameter was assessed before and after the trial period. On statistical analysis the test formulation showed significant reduction in scores (p<0.05) for most of the parameters on both inter and intra group analysis, while the reduction in control group was not found to be statistically significant (p.0.05). This study lays out that Murabbā-i Zanjabīl in a dose of 5gm twice daily given for 45 days is more effective than placebo in treating NAFLD. There was no adverse effect reported during the trial. It was thus concluded that Murabbā-i Zanjabīl is effective and safe in therapeutic management of NAFLD.